Resource recovery from livestock waste: a compilation of business cases from the Global South - Sathiskumar, Abinaya; Singha, Rajdeep; Agide, Zeleke; Peña, G.; Ruiz-Bastidas, R. C.; Taron, Avinandan; Mateo-Sagasta, Javier (International Water Management Institute (IWMI). CGIAR Initiative on One Health, 2024)
Sustainable management of livestock waste in the Global South increasingly relies on resource recovery strategies that align with circular bioeconomy principles. Business models from Asia, Africa, and Latin America demonstrate three main valorization pathways: energy and biofertilizer generation, soil nutrient recovery, and feed production for aquaculture. Biogas production through biodigesters is widely adopted, ranging from household systems to large-scale public–private partnerships. Successful examples include India’s Zakariyapura and Banas plants, Ecuador’s climate-resilient biogas facilities, and Ghana’s Kumasi abattoir initiative. These models integrate waste treatment with renewable energy and organic fertilizer generation, often supported by multi-stakeholder collaboration involving governments, NGOs, and private actors. Financially, payback periods vary between 1 and 10 years depending on scale and revenue streams. Environmental benefits include reduced greenhouse gas emissions, improved waste disposal, and enhanced soil fertility. Social impacts are evident in employment creation and community empowerment, notably through women-led cooperatives and rural entrepreneurship initiatives. Key barriers include high upfront costs, limited bio-product markets, and policy or awareness gaps. Nonetheless, the cases highlight the potential of livestock waste valorization to advance rural development, food security, and climate resilience through integrated, community-based models.